Generation of Transgene-Free Semidwarf Maize Plants by Gene Editing of Gibberellin-Oxidase20-3 Using CRISPR/Cas9 - Zhang, Jiaojiao; Zhang, Xiaofeng; Chen, Rongrong; Yang, Li; Fan, Kaijian; Liu, Yan; Wang, Guoying; Ren, Zhenjing; Liu, Yunjun (Frontiers in Plant Science, 2020)
The “green revolution” gene gibberellin oxidase contributes to the semidwarf phenotype, improving product and lodging resistance. Dissecting the function of GA biosynthetic genes would be helpful for dwarf maize breeding. In this study, we edited the maize GA20ox3 gene and generated semidwarf maize plants using CRISPR/Cas9 technology. Application of exogenous gibberellin can recover the dwarf phenotype, indicating that the mutants are gibberellin deficient. The contents of GA12 and GA53 were elevated in the mutants due to the disruption of GA20 oxidase, whereas the contents of other GA precursors (GA15, GA24, GA9, GA44, and GA20) were decreased in the mutants, and the accumulation of bioactive GA1 and GA4 was also decreased, contributing to the semidwarf phenotype. Transgene-free dwarf maize was selected from T2-generation plants and might be useful for maize breeding in the future.